2018
DOI: 10.1016/j.trb.2018.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Graphical solution for system optimum dynamic traffic assignment with day-based incentive routing strategies

Abstract: This paper analyzes the dynamic traffic assignment problem on a three-alternative network with day-based incentive routing strategies by using graphical solution method. It is assumed that the cumulative count curve of vehicles is known and that the arrival rate is unimodal. The dynamic system optimum (DSO) allocation lines are first drawn based on calculus of variations. Three possible optimal allocation lines are analyzed. A day-based incentive routing strategy is designed and conditions that when and how to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…in a typical peak hour time workplace/school travel is dominated. As u i k depends on the utility function [defined by (2)], the control input u i μ i k is calculated based on the maximal achievable utility function…”
Section: Concept Of the Utility Function Of Travellersmentioning
confidence: 99%
See 1 more Smart Citation
“…in a typical peak hour time workplace/school travel is dominated. As u i k depends on the utility function [defined by (2)], the control input u i μ i k is calculated based on the maximal achievable utility function…”
Section: Concept Of the Utility Function Of Travellersmentioning
confidence: 99%
“…In general, user optimum has a higher total cost than system optimum, sometimes much higher [1]. Previous studies have shown that system optimum [2][3][4] is more difficult to achieve than user optimum [5,6]. In case of system optimum, the total utilities are maximised; meanwhile, in user optimum, the individual user utilities are maximised.…”
Section: Introductionmentioning
confidence: 99%
“…Meng et al [14] developed a multiclass, multimodal dynamic traffic equilibrium model that derives optimal travel routes and optimal departure times, which is beneficial for traffic control and dynamic route guidance. Zhao et al [15] analysed the dynamic traffic assignment problem under three types of networks based on day-based incentive routing strategies using a graphical solution and extended it for general parallel networks to demonstrate the effectiveness of the scheme. In summary, the initial research on dynamic traffic assignment mainly lies in the theory, and the model building methods and iterative updates of algorithms are the focus of scholars' attention.…”
Section: Introductionmentioning
confidence: 99%